Effectiveness and safety of Belimumab combined with standard therapy in severe active lupus nephritis requiring kidney replacement therapy: A case report and literature review - Zhang, Chengning; Zeng, Ming; Ge, Yifei; Liu, Kang; Xing, Changying; Mao, Huijuan (Frontiers in Immunology, 2022)
Lupus Nephritis (LN) is the most common manifestation of severe organ damage for systemic lupus erythematosus (SLE) patients. Severe active LN could result in acute kidney injury (AKI), which could even require Kidney Replacement Therapy (KRT). Therefore, there needs to be a more proactive and safe induction therapy to quickly and effectively control renal immune inflammation, maintain kidney function or reverse kidney damage. While multiple clinical studies have proven the efficacy and safety of Belimumab in treating SLE and LN, these studies have not included cases of severe LN requiring KRT. We observed the effectiveness and safety of Belimumab in treating four severe active LN patients undergoing KRT. With Belimumab administered at a dosage of 10mg/kg, all four patients were able to discontinue KRT with no adverse events (AEs) to date ultimately. These cases provided an excellent basis for the application of Belimumab combined with standard therapy to LN patients with a medium to severe kidney injury.